A developed conception of the sources of law: the context of the role of political justification, custom and precedent - Leszczyński, Leszek (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2023)
The study analyses the ‘developed concept of sources of law’ created by Zygmunt Ziembiński in the second half of the 1960s, which was extremely important in Polish legal theory. Its main feature is a departure from the exclusivity of treating legal regulations as a source of law. While legislative competence plays a primary role in the conception, the inclusion of a norm in the system of law is also determined by other factors. The most characteristic in this context is the presence, in addition to the rules of exegesis (interpretative, inferential and conflict-solving), of three other factors discussed in this paper: political justification (legitimizing the legal system as a whole), customs (social norms introduced into the legal system by judicial decisions) and precedent (confirming an extra-legal norm or creating a legal norm after the acceptance of such an act by legal doctrine). This is why the concept not only breaks the positivist theoretical-legal paradigm, but also creates a realistic picture of the sources used in the decision-making processes of applying the law.